Epistemological and Ethical Reflections on Artificial Intelligence as an Area of Cognitive Computing (London Journal of Research In Humanities and Social Sciences, 2024)
This paper raises some considerations about the scientific progress that enabled the development of a Computer Science's research field, the so-called cognitive computing, whose greatest achievement is the advent of Artificial Intelligence, around which research and technological creations have been radically changing the human ethos in unprecedented proportions. In addition to the approach relating to scientificity that shapes the conception of the mind as metabolism of the brain, it is also intended in this study to seek the need to reflect on such occurrences in the scope of Philosophical Ethics (Practical Philosophy), since it seems to at least epistemologically reduce the integrality of the human condition to biological manipulation. This trend has been updated in discussions about AI and machinic agency, a trend that deprives humans of their spirituality by equating them to machinic entities that seductively simulate the mechanisms of the sapiens brain.
Keywords: Auraco Tamed; Lope; indigenous body; Caupolic; hermeneutics.; textual theory; reader reception; aesthetic of reception; psychoanalytic theory; Alphonse Daudet; literary interpretation; adolescent readers; comprehension strategies; ethical appraisal; contemporary literary discourse.; Scientism; Modernity; Ethics; Cognitive Computing; Artificial Intelligence